The Influence of Transportation Management Systems and Supply Chain Integration on Business Performance with Supply Chain Performance as a Mediating Variable in the Automotive Industry in Indonesia - Nurmasari, Wahyu; Dewayana, Triwulandari Satitidjati; Sentosa, Wahyuningsih; Yulansa, Faradisa (Dinasti Publisher, 2025)
The study explores the impact of Transportation Management Systems and supply chain integration on business performance in Indonesia's automotive industry, emphasizing how strong integration enhances operational efficiency and competitiveness. It aims to provide insights for company management, investors, regulators, and academicians, contributing to a deeper understanding of Supply Chain Management strategies and their effects on business outcomes. This study examines the impact of Transportation Management System (TMS) and supply chain integration (SCI) on business performance, mediated by supply chain performance (SCP), within the Automotive Industry in Indonesia, using a 5-point Likert scale questionnaire and validated indicators to ensure reliability and validity. The research found that Transportation Management System (TMS) has a positive and significant impact on business performance (BP), enhancing automotive companies' performance in Indonesia. Conversely, Supply Chain Integration (SCI) negatively affects business performance, suggesting that higher integration can reduce performance. However, when both TMS and SCI are mediated by supply chain performance (SCP), the results improve significantly, indicating that effective management of these variables can enhance company performance through better supply chain outcomes.